Penerapan problem based learning berbantuan media game edukasi untuk meningkatkan pemahaman konsep matematika tentang pecahan pada siswa kelas III sekolah dasar - Amalia, Dinda Setia; Poerwanti, Jenny Indrastoeti Siti; Chumdari, Chumdari (Didaktika Dwija Indria, 2025)
The goals of this research are: 1) to describe the application of the Problem based learning (PBL) model with educational game media to increase understanding of concepts; 2) improve the ability to understand mathematical concepts about fractions. This research uses a collaborative qualitative Classroom Action Research type approach. Data was collected through observation, interviews, tests and documentation. Data were analyzed through technical triangulation and source triangulation. The model used for triangulation is the Miles and Huberman model which starts from data collection, data reduction, data presentation to drawing conclusions. There were two research subjects, the class teacher and 20 students. The results of this research showed the success of increasing the average concept understanding score in cycle I = 73,6 which increased in cycle II = 86,7. The theoretical implications of this research can provide insight into facilitating the ability to understand mathematical concepts involving student-centered learning models with the help of relevant learning media. Meanwhile, the practical implication is that it provides a good improvement for mathematics learning, especially in the ability to understand concepts